2021
DOI: 10.1096/fj.202100862r
|View full text |Cite
|
Sign up to set email alerts
|

Inosine monophosphate and inosine differentially regulate endotoxemia and bacterial sepsis

Abstract: Inosine monophosphate (IMP) is the intracellular precursor for both adenosine monophosphate and guanosine monophosphate and thus plays a central role in intracellular purine metabolism. IMP can also serve as an extracellular signaling molecule, and can regulate diverse processes such as taste sensation, neutrophil function, and ischemia-reperfusion injury. How IMP regulates inflammation induced by bacterial products or bacteria is unknown. In this study, we demonstrate that IMP suppressed tumor necrosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 71 publications
(141 reference statements)
0
19
0
Order By: Relevance
“…Uracil has been shown as the intermediate metabolite to neuroprotection and neuroinflammation ( Lecca and Ceruti, 2008 ). Adenine and pseudouridine could cause inflammation; however, other nucleotides and derivatives (inosine, guanosine, pyridoxamine, and cyclic AMP) have anti-inflammatory effects ( Gerbatin et al, 2017 ; Itokawa et al, 2018 ; Veremeyko et al, 2018 ; Lovaszi et al, 2021 ) that decrease as SAE progresses. This result suggested that the metabolites could not affect the anti-inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Uracil has been shown as the intermediate metabolite to neuroprotection and neuroinflammation ( Lecca and Ceruti, 2008 ). Adenine and pseudouridine could cause inflammation; however, other nucleotides and derivatives (inosine, guanosine, pyridoxamine, and cyclic AMP) have anti-inflammatory effects ( Gerbatin et al, 2017 ; Itokawa et al, 2018 ; Veremeyko et al, 2018 ; Lovaszi et al, 2021 ) that decrease as SAE progresses. This result suggested that the metabolites could not affect the anti-inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…HPLC/MS was used to detect the difference in metabolic profiles between the two g r o u p s . I n o s i n e , r e p o r t e d a s a m e t a b o l i t e w i t h immunomodulatory effects (13,14), was found to be highly altered between the DRB1*04:05 positive and negative groups. There are few reports on inosine in AIH.…”
Section: Introductionmentioning
confidence: 92%
“…Inosine has been reported by several groups to interact with ARs (e.g., with A 2A AR and A 3 AR) but only at very high, nonphysiologic concentrations (>100 μ M) ( Welihinda et al, 2016 ). On the other hand, inosine ( Lovászi et al, 2021 ) as well as the nucleoside guanosine ( Di Liberto et al, 2016 ) clearly show pharmacological effects, at least some of which seemed to be exerted by interaction with GPCRs. However, it is unlikely that these effects are mediated by direct activation of ARs.…”
Section: Receptor Ligands (For Structures See Figs 1 ...mentioning
confidence: 99%